The Impact of Green Products on the Performance and Sustainabiity of Small and Medium Enterprises in Abuja, Nigeria - Iborida; Emmanuel Ajibade (Britain International for Academic Research (BIAR) Publisher, 2026)
Brand innovation is a critical strategic lever in highly competitive markets, yet its empirical link to economic outcomes in emerging telecommunications sectors remains underexplored. This study examines the economics of brand innovation and its impact on market efficiency in Nigeria’s telecommunications sector, drawing on evidence from South-West Nigeria. Grounded in Schumpeter’s Theory of Innovation and Porter’s Competitive Forces Model, the research analyzes how product, process, positioning, and paradigm innovations influence allocative, productive, and dynamic efficiency. A descriptive and causal research design was employed, collecting primary data from 400 subscribers via structured questionnaires, complemented by secondary data from the Nigerian Communications Commission (NCC). Data were analyzed using descriptive statistics, correlation, and multiple regression. Findings reveal that brand innovation has a statistically significant positive impact on market efficiency (β = 0.409, p < .001), explaining 52.1% of its variance. Process and paradigm innovations were identified as the most potent drivers, highlighting the importance of operational excellence and business model transformation. The results further indicate that competitive intensity and regulatory frameworks mediate the translation of innovation into tangible efficiency gains. This study provides novel empirical evidence from an African context, demonstrating that strategic brand innovation is a key determinant of market efficiency. It offers practical insights for telecom operators to prioritize impactful innovations and recommends that regulators foster innovation-friendly policies to enhance sectoral performance and consumer welfare.